The equilibrium moisture content of low-density thermal insulating materials/Lengvų termoizoliacinių medžiagų nuostovusis drėgnis - Gnip, Ivan; Vėjelis, Sigitas; Keršulis, Vladislovas (Journal of Civil Engineering and Management, 2001)
Data about water vapour sorption by modern low-density thermal insulating materials are very scarce. The isothermal sorption of water vapour dependent on relative air humidity was investigated for rock and glass wool products in this paper as well as for expanded and extruded polystyrene slabs and cellulose fibre produced in Lithuania, Poland and Estonia. The moisture in these materials is bound by several ways, therefore it is not possibile to express the equilibrium moisture Wp dependency on relative air humidity ϕ by an exact analytical equation [1, 6]. These dependencies were expressed by a two-constant empiric equation (1) for interval ϕ from 0 to 0,97 based on BET equations [1, 7, 8]. The experimental data are given in Figs 1–9, statistical treatment of this data results are given in Tables 1–3. The two fields are typical for all isothermal sorption curves: 0